1994
DOI: 10.1136/bmj.309.6953.509
|View full text |Cite
|
Sign up to set email alerts
|

Value of screening for secondary causes of hyperlipidaemia in general practice

Abstract: on 10 films taken at least one week apart were 0 7 mm for the length of the hip axis; 0-6 mm for the length of the femoral neck; and 0 7 mm for the width of the femoral neck. All the measurements were made by one observer (KC).Results were analysed by Student's t test with the programmes of the SAS Institute (Cary, North Carolina).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A comprehensive clinical and biochemical assessment is important to reveal the possible cause(s) of the dyslipidaemia where secondary lipaemia may be involved [24][25][26], thus affording a potential cure. Nawawi et al [27] reported that possible underlying causes of lipaemia were detected in a majority of elderly Caucasian referrals to a cardiovascular lipid service.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive clinical and biochemical assessment is important to reveal the possible cause(s) of the dyslipidaemia where secondary lipaemia may be involved [24][25][26], thus affording a potential cure. Nawawi et al [27] reported that possible underlying causes of lipaemia were detected in a majority of elderly Caucasian referrals to a cardiovascular lipid service.…”
Section: Discussionmentioning
confidence: 99%
“…44 Although the prevalence of secondary causes would therefore appear to be low overall, the prevalence of laboratory abnormalities that may be relevant to lipid management is far greater. The prevalence of secondary causes appears to be considerably greater as lipid parameters rise.…”
Section: Post-test Assessmentmentioning
confidence: 99%
“…The effectiveness of screening for hypothyroidism at lower cholesterol concentrations is unclear, but screening would seem justifiable in patients with more severe disease. Secondary conditions associated with hyperlipidaemia seem to be rare in general practice populations11 but more common in hospital clinics. The tests recommended for patients whose lipids are within the population reference range are justified in patients who are being assessed for lipid lowering treatment on the basis of having additional coronary risk factors and risk factors.…”
Section: Evidence Notementioning
confidence: 99%